2015
DOI: 10.1111/ele.12456
|View full text |Cite
|
Sign up to set email alerts
|

Intransitive competition is widespread in plant communities and maintains their species richness

Abstract: Intransitive competition networks, those in which there is no single best competitor, may ensure species coexistence. However, their frequency and importance in maintaining diversity in realworld ecosystems remains unclear. We used two large datasets from drylands and agricultural grasslands to assess: 1) the generality of intransitive competition, 2) intransitivity-richness relationships, and 3) effects of two major drivers of biodiversity loss (aridity and land-use intensification) on intransitivity and spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

22
234
5
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 164 publications
(267 citation statements)
references
References 48 publications
(170 reference statements)
22
234
5
6
Order By: Relevance
“…An increasing number of studies have shown that competitive relationships between plant species are not hierarchical but intransitive (de Kroon et al 2012;Soliveres et al 2015). Dynamics are obviously orders of magnitude slower than in bacterial communities but, interestingly, long-term observations have revealed patchy dynamics of grassland species that are reminiscent of those of the bacterial patches in petri dishes.…”
Section: Global Stability In Hyper-diverse Plant Communities Consistementioning
confidence: 99%
“…An increasing number of studies have shown that competitive relationships between plant species are not hierarchical but intransitive (de Kroon et al 2012;Soliveres et al 2015). Dynamics are obviously orders of magnitude slower than in bacterial communities but, interestingly, long-term observations have revealed patchy dynamics of grassland species that are reminiscent of those of the bacterial patches in petri dishes.…”
Section: Global Stability In Hyper-diverse Plant Communities Consistementioning
confidence: 99%
“…Thus, the structure of the competitive network-that is, the complete set of pairwise competitive outcomes among species (14)-should play an important role in the BEF relationship by dictating the nature and intensity of competitive interactions (and corresponding functional costs) exhibited across species in the community. Although the structure of the competitive network is increasingly acknowledged as an important driver of biodiversity and coexistence in competitive communities (14)(15)(16), whether or not the competitive network likewise affects ecosystem function remains largely untested.…”
mentioning
confidence: 99%
“…We focus on two measures of the competitive network: (i) competitive intransitivity (a continuous measure of the extent to which the community exhibits rockpaper-scissors relationships) and (ii) mean competitive ability (a continuous measure of how competitive the individuals in the community are, based on fully factorial pairwise interactions). These two properties were selected because of their importance in determining biodiversity and coexistence patterns across systems (15)(16)(17). We use a saprotrophic basidiomycete fungal community for several reasons.…”
mentioning
confidence: 99%
“…Therefore, GAM performed better on the low richness area than on the high richness area. Another reason is that stronger interspecific and intraspecific competitions might exist in communities with high species richness [36]. Biotic factors play an important role in shaping the species richness pattern in high richness areas.…”
Section: Performance Of Generalized Additive Modelmentioning
confidence: 99%